Modern furniture : 150 years of design - Albus, Volker; Bley Thomas, S.; Borka, Max; Erlhoff, Michael (Königswinter : h.f.ullmann, 2009)
Today-2000: Rocking postmodernism - Myto / Konstantin Grcic -- Limited editions - Unlimited possibilities -- 1999-1990: Sustainable design -- A short history of design fairs and events -- Bundled drawers - Tejo Remy's Chest of drawers -- 1989-1980: How do we sit? From the Well tempered chair to the Big easy / Ron Arad -- Andrea Branzi's Animali domestici - Post-apocalyptic survival props -- Natural urban gemütlichkeit - New German design in the 1980s -- Agent provocateur - Philippe Starck's Chair Costes -- Memphis - surpassing mere representation -- White and ubiquitous - monobloc chairs -- 1979-1970: Simply Billy -- Domestic landscapes -- Ettore Sottsass Jr. and His Mobili Grigi - a tomb for modernism -- 1969-1960: An unpretentious icon - Robin Day's polyprop chair -- Arne Jacobsen - Swan & egg -- 1959-1950: Castiglioni - focusing on individual objects -- Particleboard -- 1949-1940: A thoroughly modern material - Ray and Charles Eames' plywood experiments -- 1939-1930: The history of design in a nutshell - Into a natural network -- Erich Dieckmann - nature's own steel -- 1929-1920: The cantilever chair -- Neues bauen, new forms of living, new man - furniture from the Bauhaus workshops -- The chair as a manifesto -- 1919-1900: Josef Hoffmann - Sitzmaschine -- 1899-1859: The history of art-nouveau furniture -- Michael Thonet's bentwood furniture
Engels, Frans, Nederlands
boek